Über Finnlands rezente und subfossile Diatomeen V - K. Mölder; R. Tynni (Bulletin of the Geological Society of Finland, 1971)
The article deals with the distribution and ecology of the Thalassionema, Asterionella, Amphicampa, Peronia, Eunotia and Actinella species known in Finland.